Моделювання інформаційно-документальної системи презентації освітніх компонент освітньої програми - Качурівський, В. О.; Качурівська, Г. М.; Kachurivskyi, V.; Kachurivska, Н. (ЦНТУ, 2022)
У статті представлено концепцію моделі інформаційно-документальної системи з презентації документів освітніх компонент освітньої програми у вигляді дорожньої карти здобуття освіти. Розроблено модель бази, описано сутності та їх атрибути, встановлено відношення між ними для оперативного менеджменту. Визначено користувачів системи та встановлено їх ролі. Розроблено діаграму прецедентів та проведено групування їх за ролями. Запропоновано послідовність взаємодії об’єктів у часі для програмування функціоналу. The article presents the concept of the information and documentation system model for the presentation of documents of the educational components of the educational program in the form of a road map for obtaining an education. This system contributes to the implementation of the principle of openness and publicity in the activities of the institution of higher education. The function of communicative management is assigned to the information system. The database model was developed, the entities and their attributes were described, and the relationship between them was established for operational management. A list of the following entities is defined: educational component, educational program, department, semester of study, year belonging, specialty. Each entity has its own attributes and relations that make up the database. When designing the database, we defined the following relations: one educational program corresponds to a set of educational components; several educational programs can be implemented in one specialty; one department can provide the study of several educational components; a document of one educational component may belong to more than one educational program; one educational component may correspond to several academic semesters. To identify the file of the educational component, the methods of file storage organization and file name encryption rules defined by the authors were used. Working with the information system requires defining user roles and delimiting their access rights to functional services. Users of this system are assigned the following roles: developer, administrator, manager, user. A diagram of precedents was developed and their grouping by roles was carried out. The sequence of interaction of objects in time for programming the functionality of the system is proposed. The technically presented information system must be implemented using computer equipment and information technologies based on client-server architecture with further integration on the official website of the educational institution or as an independent information system. The software implementation of the information system is based on the LAMP stack.
Modeling of the Information and Documentation System for the Presentation of the Educational Components of the Educational Program
Keywords: моделювання; інформаційна система; студентоцентризм; база даних; діаграма прецедентів; діаграма послідовностей; modeling; information system; student-centeredness; database; precedent diagram; sequence diagram